PENGARUH PENAMBAHAN FENOL FORMALDEHIDA TERHADAP SIFAT HARDBOARD KAYU CAMPURAN BERDASARKAN PENGELOMPOKAN BERAT JENIS - Rena M Siagian (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
This paper deals with an experiment on the effect of phenol formaldehyde binder on the properties of hardboard. The boards were made of mixed wood species of five specific gravity groups i.e. < 0.30; 0.31-0.45; 0.46-0.60; 0.61-0.75 and > 0.75.Pulping employed in the experiment was the hot caustic soda, and the sheets were formed by using the laboratory wet felting process. The phenol formaldehyde blended at pulp slurry and presipitated by adding alum to reach pH ± 7.2. The amount of phenol formaldehyde added during sheet formation was made at 1, 1.5, and 2 percent based on the oven dry pulp.The experimental result indicated that a quality panels could be obtained by adding 1. 5 percent of phenol formaldehyde binder. Increasing the phenol formaldehyde binder up to 2 percent did not improved the physico-mechanical properties of the board produced. The experiment also shows that better physico-mechanical properties of hardboard sheets were obtained from 0.30 up to 0.60...0.75 specific gravity groups. The panels made of wood with specific gravity more than 0.75, appeared to have inferior quality.